2020
DOI: 10.3390/app10061933
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Emission Burst Extraction for Multi-Level Leakage Detection in a Pipeline

Abstract: Acoustic emission bursts are signal waveforms that include a number of consecutive imbrication transients with variable strengths and contain crucial information on the leakage phenomenon in a pipeline system. Detection and isolation of a burst against the background signal increases the ability of a pipe’s fault diagnosis system. This paper proposes a methodology using the Enhanced Constant Fault Alarm Rate (ECFAR) to detect bursts and exploit the burst phenomenon in acoustic emission. The extracted informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…The carried out measurements showed that the test object meets the requirements for pass-by noise specified in the TSI Noise (80 dB for vehicles traveling at 80 km/h). According to the TSI Noise guidelines, the obtained results for high-speed vehicles traveling at 200 km/h were normalized to the reference speed (80 km/h) by means of Equation (9). Based on the calculations performed, the tested high-speed vehicles obtained values of 76 dB for the straight section and 77 dB for the curve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carried out measurements showed that the test object meets the requirements for pass-by noise specified in the TSI Noise (80 dB for vehicles traveling at 80 km/h). According to the TSI Noise guidelines, the obtained results for high-speed vehicles traveling at 200 km/h were normalized to the reference speed (80 km/h) by means of Equation (9). Based on the calculations performed, the tested high-speed vehicles obtained values of 76 dB for the straight section and 77 dB for the curve.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that the occurrence of noise, or acoustic emission, can also bring many benefits. Acoustic emission analysis is used in many sectors of transport and industry, among others, to detect and monitor damages, leaks, fatigue, or structural analysis of various materials (e.g., concrete, plastics, wood, ceramics) [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…According to a study by the Plastic Pipe Database Committee (PPDC) of the United States, design and installation errors account for the largest proportion of PVC pipe failure causes, followed by material defects (Figure 2), meaning that inappropriate pipe products with working pressure specifications that do not meet the requirements were selected and installed in the pipe engineering design and construction. In addition, several researchers have found that extreme water pressure caused by water hammers is one of the most common factors affecting PVC pipe bursts [10][11][12][13]. For the ultimate strength analysis, the burst pressure of a pipe is an important parameter in PVC pipeline design and safe operation, which is determined as the internal water pressure resulting in pipe rupture.…”
Section: Introductionmentioning
confidence: 99%
“…Several kinds of techniques, including acoustic emission (AE) [4], vibration monitoring [5,6] and cavity dynamic pressure [7], have been used for the detection of valve internal leakage. Among these techniques, AE has witnessed a wide application in the detection of valve internal leakage both qualitatively and quantitatively, because it possesses the advantage of nonintrusive, high sensitivity and strong anti-interference ability [8][9][10]. As the accurate prediction of internal leakage Appl.…”
Section: Introductionmentioning
confidence: 99%